The Intentions of Corporate Social Responsibility: Lessons from the Life Assurance Industry in the Developing Countries - Mberewere, Simbai; Kudzanai, Matowanyika; Tinashe, Ruvinga (CV. Literasi Indonesia, 2025)
Corporate social responsibility (CSR) has become an essential aspect of business operations globally. Companies are increasingly expected to demonstrate their commitment to social and environmental causes, beyond their financial obligations. Despite the growing importance of CSR in the industry, there is a lack of understanding of the motivations driving CSR initiatives, and the implications of these initiatives for stakeholders. This systematic review aims to unpack the intentions behind CSR initiatives in the life assurance industry, exploring the economic, legal, ethical, philanthropic, and environmental motivations driving these initiatives. A systematic review of existing literature was conducted, searching major databases including Scopus, Web of Science, and Google Scholar, resulting in the inclusion of 30 studies published between 2000 and 2020. The review reveals that CSR initiatives in the life assurance industry are driven by multiple intentions, including economic intentions such as improving financial performance and increasing competitiveness, legal intentions such as complying with regulatory requirements, ethical intentions such as promoting social justice and reducing inequality, philanthropic intentions such as giving back to society, and environmental intentions such as reducing carbon footprint and promoting sustainability. His systematic review of existing literature on CSR in the life assurance industry revealed that CSR initiatives were characterized by a range of intentions, including economic, legal, ethical, philanthropic, and environmental intentions. The findings suggested that companies engaged in CSR activities for multiple reasons, including improving their financial performance, complying with regulatory requirements, promoting social justice, giving back to society, and reducing their environmental impact. The study's findings had implications for policymakers, practitioners, and researchers. Policymakers could use these findings to develop regulations that encourage companies to engage in CSR activities that prioritize social and environmental benefits. Practitioners could use these findings to develop CSR strategies that balance financial gains with social and environmental benefits. Researchers could use these findings to develop new theories and frameworks that explain the complexities of CSR intentions.